Aflatoxin M1 in fresh dairy milk from small individual farms in Indonesia - R. Widiastuti; Y. Anastasia (Indonesian Center for Animal Research and Development (ICARD), 2018)
This present study was aimed to investigate the presence of aflatoxin M1 (AFM1) residue in fresh dairy milk collected from small dairyl farms. A total of 104 samples of fresh cow's milk were collected in Pengalengan-Bandung and Sukabumi (West Java province), and Tanggamus (Lampung province) in April and September 2012. All samples were analyzed by a high performance liquid chromatography and detected with fluorescence detector after extraction with organic solvents. Contamination of AFM1 was found on 1.96% (1/51) from the samples collected in April 2012 at concentration of 1.20 ng/L and 39.63% (21/53) from the samples collected in September 2012 at concentration of 1.20 ng/L 1.0 – 34.1 ng/L. Those positive samples were obtained from Pangalengan and Sukabumi, but none for those samples collected from Tanggamus both on collection time April nor September 2012. In those positive samples for AFM1, there is no sample contained AFM1 above the maximum level (ML) regulated in Indonesia (500 ng/L or 0.5 µg/L). Low contamination levels of AFB1 in the range of 0.38 to 6.64 µg/kg found in supplemental feed samples from the same sampling time and locations. The findings of AFM1 contamination in raw fresh milk from this study caused no harm to the consumers. However, regular monitoring on the presence of AFM1 in dairy milk and aflatoxin B1 (AFB1) in dairy cattle feed is necessary to ensure the protection of human health.